2011
DOI: 10.2527/jas.2010-3463
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the pathogenesis of cystic follicles in cattle: Microarray analysis of gene expression in granulosa cells1

Abstract: Ovarian follicular growth and development are regulated by extraovarian and intraovarian factors, which influence granulosa cell proliferation and differentiation. However, the molecular mechanisms that drive follicular growth are not completely understood. Ovarian follicular cysts are one of the most common causes of reproductive failure in dairy cattle. Nevertheless, the primary cause of cyst formation has not been clearly established. A gene expression comparison may aid in elucidating the causes of ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 131 publications
4
48
0
Order By: Relevance
“…However, numerous studies have shown that cysts are not simply inactive persistent structures but are in fact the contrary, still evolved, with important metabolic activity and structural changes , Monniaux et al 2008, Ortega et al 2008, Grado-Ahuir et al 2011, Rodríguez et al 2011. Also, other authors have found similar changes in the protein and mRNA expression of ESR2 isoforms in follicular cysts in women with polycystic ovary syndrome compared with normal size-matched follicles in healthy women (Jakimiuk et al 2002), and in prenatal testosterone-treated ovine females characterized by follicular persistence (Ortega et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…However, numerous studies have shown that cysts are not simply inactive persistent structures but are in fact the contrary, still evolved, with important metabolic activity and structural changes , Monniaux et al 2008, Ortega et al 2008, Grado-Ahuir et al 2011, Rodríguez et al 2011. Also, other authors have found similar changes in the protein and mRNA expression of ESR2 isoforms in follicular cysts in women with polycystic ovary syndrome compared with normal size-matched follicles in healthy women (Jakimiuk et al 2002), and in prenatal testosterone-treated ovine females characterized by follicular persistence (Ortega et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…The bovine CYP11A1 and FGF9 primer and probe sequences and information are described by Lagaly et al (2008) and Grado-Ahuir et al (2011) respectively. The bovine CYP17A1, STAR, and LHCGR primer and probe sequences are described by Spicer et al (2008).…”
Section: Rna Extraction and Rt-pcr For Mrna Quantificationmentioning
confidence: 99%
“…Furthermore, the RT-PCR products were run on agarose gels to verify the length and size of the expected target genes, and the same RT-PCR cDNA samples were sequenced to verify the amplified product. Target gene expression was normalized to constitutively expressed 18S rRNA and relative quantity of target gene mRNAs was expressed as 2 KDDCt using the relative comparative threshold cycle method as described previously (Lagaly et al 2008, Grado-Ahuir et al 2011). …”
Section: Rna Extraction and Rt-pcr For Mrna Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This disorder is a significant cause of reproductive losses with great economic impact on dairy farms. The incidence of COF is high, since in many herds this disorder has been estimated at 10%-30% of the population (10,22,28). Economic losses are caused by an increase in the number of days open, increased culling rate because of infertility, and high treatment costs (8).…”
Section: Introductionmentioning
confidence: 99%